Cascade excitation of vortex motion and reentrant superconductivity in flexible Nb thin films. (1st April 2023) - Zhang 张, Liping 丽萍; Xu 徐, Zuyu 祖雨; Li 黎, Xiaojie 晓杰; Zhang 张, Xu 旭; Qin 秦, Mingyang 明阳; Zhang 张, Ruozhou 若舟; Xu 徐, Juan 娟; Cheng 程, Wenxin 文欣; Yuan 袁, Jie 洁; Wang 王, Huabing 华兵; Silhanek, Alejandro V.; Zhu 朱, Beiyi 北沂; et al.
Abstract : High quality Nb films were successfully prepared on both flexible polyimide (PI) and rigid Al2 O3 substrates and their transport properties were systematically studied at various applied currents, external magnetic fields, and sample orientations. It is found that a curved Nb/PI film exhibits quite different superconducting transition and vortex dynamics compared to the flat Nb/Al2 O3 film. For the curved Nb/PI film, smooth superconducting transitions were obtained at low currents, while unexpected cascade structures were revealed in the ρ ( T ) curves at high currents. We attribute this phenomenon to the gradient distribution of vortex density together with a variation of superconductivity along the curved film. In addition, reentrant superconductivity was induced in the curved Nb/PI thin film by properly choosing the measurement conditions. We attribute this effect to the vortex pinning from both in-plane vortices and out-of-plane vortices. This work reveals the complex transport properties of curved superconducting thin films, providing important insights for further theoretical investigations and practical developments of flexible superconductors.